‘Now it tells you to press continue’: multimodal strategies for navigating between machine-human and human-human instructions in Thermomix® experience meetings - Dix, Carolin (Frontiers in Communication, 2025)
This paper focuses on the interactive multimodal management and orchestration of human-to-human instructions and machine-to-human instructions when learning how to use the smart cooking aid Thermomix® during cooking experience meetings. These peer-to-peer events, hosted in private homes, combine elements of cooking workshops, product presentations, and sales events. Unlike traditional cooking classes, cooking experience meetings involve a human (the representative) and a machine which both give instructions to the participants. The study focuses on how Thermomix® representatives as experts spatially and interactively position themselves as intermediary between the machine and the users and at the same time as authoritative and legitimate instructors. The examples show how they coordinate their instructions with the digital guidance provided by the machine, elaborate these instructions or add new ones. Using video data from two cooking experience meetings, the analysis shows that while the Thermomix® provides step-by-step directives, the representative plays a crucial role in explaining, evaluating, and adapting the instructions to ensure participants understand the cooking process. The study contributes to research on human-machine interaction by illustrating how instructional authority is distributed between human experts and smart technology in interactive learning environments.